Prison break: a crime of doubtful constitutionality (2023)
This article analyzes the constitutionality of Article 448 of the Colombian Penal Code, which criminalizes prison breaks, in light of the principles of the 1991 Political Constitution and the fundamental pillars of a Social State of Law such as Colombia. To this end, the arguments offered to justify the offense and the considerations made to oppose it are analyzed, concluding which of them best fits the Colombian constitutional model.